The role of complete exomic sequencing in the administration of targeted drugs in patients with multiform glioblastoma - A. V. Kaminskiy; N. P. Zverev; A. A. Lyakhovets; D. R. Naskhletashvili; M. A. Gairyan; A. A. Isaev; D. N. Khmelkova; I. L. Plaksa (Опухоли головы и шеи)
Introduction. Glioblastoma is the most common primary malignant glial tumor of the brain in adult patients. Median overall survival for this pathology varies between 3 and 12 months, and only 5 % of patients live for more than 5 years. Current treatment methods allow to slightly increase lifespan of the patients with glioblastoma but not in all cases.Aim – to determine the utility of full exome sequencing of biopsy materials of patients with glioblastoma using expanded gene panel for prescription of new targeted therapy.Materials and methods. The study included 28 patients with glioblastoma multiforme. Foundation One CDx assay was performed using DNA extraction from a paraffin block and next-generation sequencing. In total, 4 classes of genomic changes in 324 genes, introns of 34 genes taking part in rearrangements, as well as microsatellite instability and tumor mutation load were evaluated. For every tumor profile, individual therapy options were identified in accordance with the current knowledge, references for the relevant scientific studies were included. From some patients, feedback was received allowing to evaluate the dynamics of their condition and changes in therapy after the performed study.Results. Genes in which mutations are the most common were identified: EGFR – in 11 patients, CDKN2A – in 13, TP53 – in 9, TERT (frequent mutations in TERT gene promoters с.-124C>T and c.-146C>T) – in 15, MTAP – in 10. Mean mutation level was 4.5 mutations/ MB and tumors did not have microsatellite instability. For 6 patients, appropriate targeted therapy was identified.Conclusion. Sequencing using an extended gene panel is justified and recommended for patients with glioblastoma multiforme for selection of new targeted therapy.